Audit Kualitas Perangkat Lunak: Verifikasi Fungsionalitas Sistem Presensi Berbasis Web Menggunakan Standar ISO/IEC 29119 - Nurul Khotimah; Dodi Wagiyanto; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
The reliability of employee attendance systems is a crucial element in human resource management to ensure payroll data integrity and discipline, yet the transition from manual methods to web-based digital platforms often faces data validity challenges, particularly regarding vulnerabilities to user time manipulation (client-side manipulation) and data redundancy. This study aims to audit the software quality of a web-based attendance application built using Native PHP and MySQL database, with a primary focus on verifying the stability of the system's logic in handling server-side time and validating the attendance workflow sequence. The testing methodology adopted adheres to the ISO/IEC 29119 international standard using a Black Box Testing approach, where a total of 25 test cases were comprehensively designed covering user interface modules, check-in and check-out logic, database integrity, and input security using Boundary Value Analysis and Stress Testing techniques. The results demonstrate that the system achieved a 100% success rate (Pass Rate) with a